Can neighbourhoods save the city? : community development and social Innovation - Moulaert ,Frank; Gonzalez, Sara (Routledge, Oxon, 2010)
For decades, neighbourhoods have been pivotal sites of social, economic and political exclusion processes, and civil society initiatives, attempting bottom-up strategies of re-development and regeneration. In many cases these efforts resulted in the creation of socially innovative organizations, seeking to satisfy the basic human needs of deprived population groups, to increase their political capabilities and to
Social innovation and community development -- Historical roots of social change -- Almolin -- Social innovaton in the wake of urban movement -- Building a shared interest -- How to make neighbourhoods act --Social inclusion and exslusion in the neighbourhood -- Arts factory in ferndale -- The ouseburn trst in newcastle-- Autonomy and inclusive urban governance -- the end of social innovation in urban development -- Creatively designing urban futures -- Socially innovative projects
Keywords: Neighbourhoods; Développement communautaire urbain; Quartiers -- (Urbanisme) -- Aspect social